Intensified Aridity Hinders Soil Microbes From Improving Their Nitrogen Use Efficiency - Jingyi Yang; Zitong Wang; Ziping Liu; Qing Chang; Bo Wang; Yangjian Zhang; Edith Bai (Global Change Biology, 2025)
Microbial nitrogen (N) use efficiency (NUE) is crucial for retaining N in soils and supplying N to plants. However, how soil microbial NUE in N‐limited dryland responds to aridity remains poorly understood. Here we used 18 O and 15 N isotope labeling techniques to investigate the effects of climatic, edaphic, and biotic factors on microbial N metabolism along a 2200 km aridity gradient on the Tibetan Plateau. We found soil microbes could enhance their NUE to cope with N limitation, but this ability was hindered when aridity index (AI) 0.12), microbes increased their NUE with decreasing aridity because they got more limited by N and temperature. The increase of microbial NUE increased microbial necromass N, contributing to the increase of soil total N. Our findings provide new insights into microbial N use strategies under water‐ and N‐limited conditions and their vital role in N retention in ecosystems. This helps to deploy microbial potential in conserving N in soils for higher productivity and to better predict soil N processes under global changes.